2019
DOI: 10.1101/588673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioremediation of soils contaminated with petroleum solid wastes and drill cuttings byPleurotussp. strains under different treatment scales

Abstract: Wastes from the oil industry represent one of the sources of soil pollution with the greatest environmental impact. Both drill cuttings and crude residues are delivered to the soil and produce severe toxic effects, mainly due to the presence of polycyclic aromatic hydrocarbons. Various bioremediation technologies have been implemented in order to restore the soil quality and the natural auto depuration capabilities, amongst them: composting, bioaugmentation and biostimulation. All of these bioremediation techn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Also, we annotated the representative genome of Pleurotus ostreatus in the KEGG database [11], and observed that some sequences of the aromatic compound metabolism showed signatures of functional redundancy within the genome. In addition, these results extend the scope of a prior prepublication posted on bioRxiv server describing our early experimental research findings [12].…”
Section: Introductionsupporting
confidence: 77%
“…Also, we annotated the representative genome of Pleurotus ostreatus in the KEGG database [11], and observed that some sequences of the aromatic compound metabolism showed signatures of functional redundancy within the genome. In addition, these results extend the scope of a prior prepublication posted on bioRxiv server describing our early experimental research findings [12].…”
Section: Introductionsupporting
confidence: 77%